Annual dialysis data report 2022, Japanese Society for Dialysis Therapy (JSDT) Renal Data Registry - Norio Hanafusa; Masanori Abe; Nobuhiko Joki; Junichi Hoshino; Masatomo Taniguchi; Kan Kikuchi; Takeshi Hasegawa; Shunsuke Goto; Tetsuya Ogawa; Eiichiro Kanda; Shigeru Nakai; Toshihide Naganuma; et al. (Renal Replacement Therapy)
Abstract The annual survey of the Japanese Society for Dialysis Therapy Renal Data Registry (JRDR) was sent to 4521 dialysis facilities at the end of 2022, among which 4464 facilities (98.7%) responded to the facility survey, and 4276 facilities (94.6%) responded to the patient survey. The number of chronic dialysis patients was 347,474 at the end of 2022, marking the first decrease since the beginning of this survey. The prevalence rate of dialysis patients was 2781 per million population. The mean age of prevalent dialysis patients in the patient survey was 69.87 years. Diabetic nephropathy was the most common primary disease among these patients (39.5%), followed by chronic glomerulonephritis (24.0%) and nephrosclerosis (13.4%). The number of incident dialysis patients during 2022 was 39,683, showing a decrease of 828 from 2021. Among incident dialysis patients, the mean age was 71.42 years, and diabetic nephropathy (38.7%) was the most common cause of end-stage kidney disease (ESKD). Nephrosclerosis replaced glomerulonephritis and was the second most common cause of EKSD. In 2022, 38,464 patients died, giving a crude annual mortality rate of 11.0%, the highest in JRDR history. This high mortality may be related to the decline in the total number of dialysis patients. The three major causes of death were infectious disease (22.6%), which replaced heart failure in 2022, heart failure (21.0%), and malignancy (7.6%). The number of patients treated by hemodiafiltration (HDF) has been rising since 2012 to reach 191,492 by the end of 2022, accounting for 55.1% of all dialysis patients. The number of peritoneal dialysis (PD) patients was 10,531 in 2022, which has slightly increased since 2017. The combination or hybrid therapy with hemodialysis (HD) or HDF was given to 20.3% of PD patients. Home HD therapy was conducted in 827 patients at the end of 2022, an increase of 79 from 2021. Comprehensive data on anemia management was collected in 2022 for the first time since 2012. Clinical data about coronavirus disease-2019 (COVID-19) and history of past living kidney donation were also investigated in 2022, as in 2021. In this report, a chapter dedicated to PD was included for the first time since 2018. The results obtained for each condition provide evidence for developing more clinically effective practice patterns for these conditions.